ASSESSING THE IMPACT OF TRAINING AND DEVELOPMENT PROGRAMS ON EMPLOYEE CAREER GROWTH AND ORGANIZATIONAL SUCCESS - Aslichah, Aslichah; Krishernawan, Indra; Widaningsih, Raden Rara Ayu (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Training and development programs have become integral components of organizational strategies aimed at fostering employee growth and driving organizational success. This literature review examines the impact of such programs on both individual career development and the broader performance of organizations. Research highlights that well-structured training programs contribute to enhancing employees' skills, knowledge, and competencies, which are essential for career progression. Furthermore, training initiatives that align with organizational goals not only improve job satisfaction but also increase productivity, innovation, and overall organizational performance. The review identifies key factors influencing the effectiveness of these programs, such as leadership support, the availability of resources, and a commitment to continuous learning. This study also explores the reciprocal relationship between employee development and organizational success, illustrating how a skilled workforce contributes to achieving long-term business objectives. The findings emphasize the need for organizations to invest in comprehensive training programs to support both individual career trajectories and organizational growth.